Are sardine larvae caught off northern Portugal in winter starving? An approach examining nutritional conditions - Chicharo, Maria Alexandra (2003)
Recently, winter upwelling events off western Iberia have become more frequent. This may affect the production and survival of sardines egss and larvae through increased offshore transport. By analysis of RNA: DNA ratios, we investigated the impact of winter upwelling events on the larval conditions of Sardina pilchardus larvaeas a function of oceanographic conditions and food availability. Larvae were collected on a research cruise off northern Portugal in February 2000. Environmental parameters such as wind, water temperature, salinity microzooplankton biomass and daily egg production of the calanoid copepod Calanus helgolandicus also measured. The mean RNA:DNA ratios wererelatively high, indicating that almost all larvae collected were good condition. This was in agreement with the high microzooplankton biomass and high daily egg production of the copepod C. helgolandicus recorded during the same period. No adverse effects of upwelling causing offshore transport of larvae into poor feeding areas could be demonstrated because of the presence of a stratified warm plume with consequent high food production.